Halal Supply Chain Analysis of a Micro-Scale Chicken Intestine Cracker Enterprise in Surabaya - Dewi, Fatimah Sari; Rahmawati, Lilik (Halal Science, 2026)
Limited integration of halal assurance across supply chain stages remains a critical challenge for Indonesian micro-scale food enterprises, particularly those processing high-risk animal-based products. Existing studies predominantly emphasize product-level certification, leaving a gap in understanding how halal supply chain management (HSCM) is operationalized at the micro-enterprise level. This study aims to analyze the implementation of HSCM in a micro-scale enterprise, Pak Rebo Chicken Intestine Crackers in Surabaya, Indonesia, using a qualitative case study approach. Data were collected through semi-structured interviews with five key participants (owner, supplier, employees, and consumer), direct observation, and documentation review. The analysis was guided by a halal supply chain framework covering production preparation, production processing, distribution, and consumption stages. Halal practices were evaluated using a five-point compliance scale adapted from prior halal supply chain studies, where scores range from 1 (very poor) to 5 (excellent) based on observable operational indicators. The findings indicate strong compliance in hygiene practices, material handling, transaction transparency, and distribution activities. However, weaknesses remain in documentation, traceability, halal labeling, and inventory control systems, indicating that halal compliance is primarily practice-based rather than system-based. This study contributes to halal supply chain literature by highlighting the gap between operational and institutional compliance in micro-scale enterprises and provides practical insights for strengthening traceability, labeling consistency, and governance mechanisms. The results offer implications for improving halal assurance systems in resource-constrained MSME contexts.